Teacher competency development in the digital age: promoting underprivileged students’ vocational skills - Suban Pornwiang; Monnapat Manokarn; Prajob Khwanmun (Institute of Advanced Engineering and Science, 2026)
Vocational skills are essential for underprivileged students, providing practical job training that enables self-sufficiency, breaks the cycle of poverty, and improves job opportunities. The study addresses a critical gap, focusing on teacher competency for underprivileged students in urban communities of Chiang Mai, ethnic minority or stateless individuals, facing complex barriers to accessing fundamental rights and services. The concept of novel transdisciplinary research, comprising 10 vocational experts, 10 academic professionals from Chiang Mai-based universities, 35 school leaders and educators, and 261 parents, selected via purposive sampling. Data were collected through focus group discussions, field observations, workshops, and structured questionnaires, and were analyzed using descriptive statistics (mean, standard deviation) and qualitative content analysis. Public participation was crucial in developing guidelines for enhancing teacher competencies. The resulting framework consists of three components: challenges encountered by teachers; teacher development curriculum covering content, developmental approaches, and collaborative development networks; and development outcomes, including eight fundamental and eight specific outputs, and outcomes for improved student quality of life, competencies, and vocational skills across defined aspects. These guidelines provide a novel framework (outputs and outcomes) that integrates socio-legal knowledge and vocational training to sustainably improve the educational experiences and quality of life of this specific target group.